Exploring the Selayarese Language Transfer on Students' English Pronunciation - Muh. Aswan Amrah Arrahman (Journal of Language, Literature and Teaching, 2022)
Indonesia consists of various tribes and possesses hundreds of distinctive native languages. Therefore, the influence of native language on English pronunciation is seen as an obstacle for Indonesian EFL learners. In Second Language Acquisition (SLA) it is classified as language transfer. Selayarese language as one of the native languages existed in South Sulawesi Province also gave positive and negative transfer towards English pronunciation. It was verified through a qualitative case study employed towards 20 students from XI IPA 5 at SMAN 1 Selayar. Several methods were undergone to obtain the data namely questionnaires and students’ recording. The result of the study revealed that Selayarese language gave major negative transfer towards English vowel /æ/ and clusters /bl/. Moreover, Selayarese language gave minor negative transfer towards English long vowels /ɑ:/, /i:/, /u:/, /ɜ:/, /ɔ:/ and vowel /ɒ/, diphthongs /əʊ/, /aʊ/, /eə/, /ɪə/ and /ʊə/, also consonants /v/, /ð/, /ɵ/, /ʃ/ and /z/. besides that, Selayarese language also gave minor positive transfer towards; English vowels /ɛ/, /ʌ/, /ʊ/, /ɪ/ and /ɔ/, diphthongs /aɪ/ and /ɔɪ/ and also consonants /b/, /d/, /g/, /h/, /dʒ/, /k/, /l/, /m/, /n/, /p/, /ŋ/, /r/, /s/, /t/, /w/ and /j/.